Modelo para el análisis de correlación de variables frente a la percepción de seguridad ciudadana en Colombia - Nieto Fagua, Edwin Alberto; Yepes Guzmán, María Camila (Universidad Antonio Nariño, 2021)
At present, multiple government organizations manage large volumes of data in their day-to-day work, which depending on its criticality are exposed or not, to the community in order for there to be greater participation by citizens and to generate transparency in its management.